Advances in data science : symbolic, complex, and network data - Diday, E.; Guan, Rong; Saporta, G. (Gilbert); Wang, Huiwen (Innovation, entrepreneurship and management series. Big data, artificial intelligence and data analysis set, 2020)
Presenting a collection of up-to-date papers by eminent scholars following two international workshops held in Beijing and Paris, this book includes fundamental contributions, as well as applications to several domains, including business and the social sciences. --